The Future Of Islamic Education: Opportunities And Challenges - Andri, Anri Saputra; Rafika Nisa; Lahmuddin Lubis; Pamonoran Siregar (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
Islamic education currently faces complex challenges amidst the current of globalization, the acceleration of digital technology, and the weakening of spiritual values among the younger generation. This study aims to explore in depth the various potentials and obstacles that influence the future direction of Islamic education. With a descriptive qualitative approach based on literature studies, this article analyzes various scientific sources, field data, and the thoughts of contemporary Islamic education figures. The results of the discussion show that the existence of global spiritual awareness, technological advances, and the spirit of integration between religious knowledge and science provide great opportunities for Islamic education to develop. On the other hand, challenges such as curriculum separation, weak mastery of technology among educators, and the influence of secularism are significant obstacles. Therefore, systemic strategies are needed such as holistic curriculum updates, improving teacher quality, wise use of technology, and strengthening moderate and universal Islamic values to realize relevant and contributive Islamic education in the modern era.